The Cambridge legal history of Australia - Cane, Peter, 1950-; Ford, Lisa, 1974-; McMillan, Mark David, 1969- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
Featuring contributions from leading lawyers, historians and social scientists, this path-breaking volume explores encounters of laws, people, and places in Australia since 1788. Its chapters address three major themes: the development of Australian settler law in the shadow of the British Empire; the interaction between settler law and First Nations people; and the possibility of meaningful encounter between First laws and settler legal regimes in Australia. Several chapters explore the limited space provided by Australian settler law for respectful encounters, particularly in light of the High Court's particular concerns about the fragility of Australian sovereignty. Tracing the development of a uniquely Australian law and the various contexts that shaped it, this volume is concerned with the complexity, plurality, and ambiguity of Australia's legal history.
Editor's introduction / Peter Cane, Lisa Ford, and Mark Macmillan -- Plural legal orders : concept and practice / Shaunnagh Dorsett -- English legal culture in the late 18th century : institutions and values / David Lieberman -- Lawful Mary / Spiers Williams -- Colonial settlement to colony / Bruce Kercher -- Colonial self government / Ann Curthoys and Jessie Mitchell -- Federation / Brendan Lim -- Constitutionalism in Australia / Cheryl Saunders -- Indigenous governance -- The challenge of indigenous polities / Kirsty Gover and Eddie Cubillo -- Australia as Empire / Miranda Johnson and Cait Storr -- Australia and the world / Coel Kirkby -- Settlement and dispossession / Lisa Ford and David Andrew Roberts -- Australian land law / Maureen Tehan -- Aboriginal land rights, subjection, and the law / Amanda Kearney -- Land justice / Jason Behrendt and Sean Brennan -- Environment / Ruth A Morgan and Judith Jones -- Colonial law and its control of aboriginal and Torres Strait islander families / Terri Libesman, Katherine Ellinghaus, and Paul Gray -- The legal history of non-indigenous marriage / Alecia Simmonds -- Protection regimes / Amanda Nettelbeck -- Economic and social welfare / Anne O'Brien -- Civil rights and indigenous people / Gary Foley and Crystal McKinnon -- Rights / Frank Bongiorno -- Citizenship and immigration / Rayner Thwaites -- Criminal law and the administration of justice in early New South Wales and Van Diemen's land / David Andrew Roberts -- Criminal justice after the convicts : a history of the long twentieth century / Andy Kaladelfos and Alana Piper -- Indigenous peoples and settler criminal law / Mark Finnane -- Civil wrongs / Mark Lunney -- Labour law / Diane Kirkby -- Place and race in Australian copyright law : May Gibbs' and Albert Namatjira's copyright / Kathy Bowrey -- Indigenous legal traditions and Australian indigenous legal traditions / Nicole Watson -- Reckoning with the past / Shino Konishi.
Title from publisher's bibliographic system (viewed on 05 Aug 2022).
Keywords: Law -- Australia -- History